MicroRNA-379-5p inhibits tumor invasion and metastasis by targeting FAK/AKT signaling in hepatocellular carcinoma. Issue 1 (28th May 2016) - Chen, Jing-Song; Li, Hua-Shu; Huang, Jiong-Qiang; Dong, Shi-Hao; Huang, Zhi-Jie; Yi, Wei; Zhan, Gao-Fang; Feng, Ju-Tao; Sun, Jian-cong; Huang, Xiao-Hui
Highlights: miR-379-5p is significantly down-regulated in HCC. miR-379-5p can inhibit HCC invasion and metastasis. FAK is a direct target of miR-379-5p. miR-379-5p exerts its functions through inhibiting FAK/AKT signaling. miR-379-5p might be a potential therapeutic target and prognostic marker for HCC. Abstract: Some microRNAs (miRNAs) have been implicated in hepatocellular carcinoma (HCC) development and progression. However, the roles and mechanisms of several miRNAs in HCC remain poorly understood. Here, we report that miR-379-5p, which is down-regulated in HCC tissues and cell lines, is associated with advanced TNM stage and metastasis in HCC. The ectopic overexpression of miR-379-5p inhibited HCC cell migration, invasion, epithelial-to-mesenchymal transition (EMT) and metastasis both in vitro and in vivo . Conversely, miR-379 knockdown increased migration, invasion and EMT in HCC cells. Moreover, miR-379-5p exerted this function by directly targeting focal adhesion kinase (FAK) 3′-UTR and repressing FAK expression, thus leading to suppression of AKT signaling. Furthermore, the tumor suppressive effects of miR-379-5p in HCC cells were reversed by activating AKT signaling or restoring FAK expression. In clinical samples of HCC, miR-379-5p negatively correlated with FAK, which was up-regulated in HCC. Taken together, our findings highlight the important role of miR-379-5p in regulating the EMT and metastasis of HCC by targeting FAK/AKT signaling, suggesting that miR-379-5p may represent a novel potential therapeutic target and prognostic marker for HCC.